Efektivitas Frekuensi dan Volume Penyemprotan Daun dengan Agens Hayati Filosfer dalam Meningkatkan Pertumbuhan Tanaman dan Hasil Padi - Khodar, Samsi Abdul; Ilyas, Satriyas; Budiman, dan Candra (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTIncreased of plant productivity in field determined by the use of quality seed from improved variety. The purpose of this research was to study the effect of frequency and volume of phyllosphere biological agents by foliar spray on rice plant infected by Xanthomonas oryzae pv. oryzae (Xoo) in improving plant growth, production of rice seed, and controlling bacterial leaf blight (BLB). This research was conducted at Seed Health Laboratory, Department of Agronomy and Horticulture, Bogor Agricultural University, and Muara Experimental Field, Rice Research Institute, March through September 2014. The experiment was conducted using a randomized complete block design with two factors, and replicates as blocks. The first factor was five levels of frequency of spraying with biological agents: P0 = control, P1 = Xoo seed inoculated then invigorated with biomatriconditioning, P2 = Xoo inoculated seed, then biomatriconditioned, and the plants were sprayed with phyllosphere biological agents F112 once, P3 = as P2, and the plants were sprayed with F112 twice, and P4 = as P2, and the plants were sprayed with F112 three times. The second factor was three levels of spray volume: i.e., 300, 400, and 500 L ha-1. Result of this experiment revealed that biomatriconditioning with rhizobacteria P. diminuta A6 and B. subtilis 5/B improved field emergence and seedling dry weight. Seeds applied with biomatriconditioning then followed by foliar spray with phyllosphere bacteria F112 at 40, 60, and 80 days after transplanting effectively reduced severity of BLB, increased plant dry weight and seed yield. All treatments increased yield as compared to untreated control. Volume of foliar application showed no significant difference, therefore, the lowest volume of 300 L ha-1 was recommended. Keywords: Bacillus subtilis 5/B, biomatriconditioning, Pseudomonas diminuta A6, Xanthomonas oryzae pv. oryzae